Monetary Policy During and After the Crisis in Korea - Dongchul Cho (Korea Development Institute (KDI), 2003)
This paper discusses Korea's post-crisis monetary policy, focusing on two questions: (i) whether the high interest rate policy right after the outbreak of crisis was effective on exchange rate stabilization and (ii) whether the post-crisis interest rate policy can be justified in light of the optimal monetary policy rule framework. In the first part, this paper presents a theoretical framework that explains how a temporarily high interest rate policy can stabilize the depreciating exchange rate through either signaling effect or unanticipated monetary shock. As for empirical evidence, the paper summarizes the existing literature showing that the results are still inconclusive, but if there is any country in Asia where the policy was effective, it is likely to be Korea. Then the paper discusses conjectures that can explain this result for Korea. In the second part, this paper discusses monetary policy objectives and implied interest rate policy rules, and how to understand the post-crisis interest rate policy of Korea by comparing calibration results of such policy rules with the actual interest rate policy. The high interest rate policy in 1998 can be justified only when the actual (year-on-year) inflation rates as opposed to expected inflation rates were used. In contrast, the low interest rate policy since 1999 can be justified only when GDP deflator as opposed to Core CPI was used. Then the paper criticizes the actual year-on-year inflation rate as an inflation index for the monetary policy, and argues that the high interest rate policy appears hard to be justified from the second quarter of 1998.
Keywords: 330